Identification and functional characterization of adhesins involved in attachment of methanogens to rumen protozoa : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Microbiology at Massey University, Palmerston North, New Zealand - Ng, Filomena (Massey University, 2016)
Symbiotic interactions are frequently observed amongst members of the complex microbial community inhabiting the fermentative forestomach (rumen) of ruminant animals. In this ecosystem, hydrogen (H2)-using methanogens can be found as ecto- and endo-symbionts of H2-producing protozoa, and this interaction contributes to ruminant methane emissions. Rumen symbionts must have the ability to attach to protozoal hosts, presumably via protozoa-binding cell surface proteins, however the identity and specificity of these proteins are not known. A protein of the methanogenic archaeon Methanobrevibacter ruminantium M1 that binds to rumen protozoa was identified using phage display technology. A large shot-gun phage display library was constructed from M1 DNA, and affinity screened by biopanning using rumen protozoa as bait. After two rounds of biopanning, a recombinant clone encoding part of a previously annotated putative adhesin, Mru_1499, was identified as a protozoa-binding protein. The protozoal binding region of the affinity selected protein was mapped, and a “reverse panning” procedure was developed to identify protozoal species that bind to the affinity selected protein. Next, the protozoa-associated methanogen and bacterial communities were characterized, and several taxa of archaea and bacteria were found to be over-represented in the protozoa-associated community relative to their abundance in the rumen contents. Adhesins from this protozoa-associated community were identified by affinity screening of a community-scale phage display library using rumen protozoa as bait, combined with high-throughput single molecule amplicon sequencing. The comparison between pre- and post-panning sequence datasets showed seven highly enriched candidate adhesin-encoding ORFs after affinity-panning of the library on protozoa as bait. In conclusion, several adhesins mediating interactions between methanogenic archaea, bacteria and protozoa were identified using phage display at both single-organism and metagenome scales. Further assays are required to verify the function of these candidate adhesins as “molecular bridges” in interactions involving rumen protozoa. This is the first report for characterization of the protozoa-associated symbiont community by next generation sequencing of the 16S rRNA gene.
Keywords: Methanobacteriaceae; Genetics; Rumen; Microbiology; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology